Improving Elementary School Students’ Learning Outcomes in Islamic Religious Education through Video-Based Instruction on the Exemplary Values of Asmaul Husna - Nanik Sugianti; Aam Amaliyah (Jurnal Indonesia Pendidikan Profesi Guru, 2026)
Background: Learning outcomes in elementary Islamic Religious Education require innovative instructional media to effectively enhance students’ understanding and engagement, particularly in teaching abstract moral and religious values such as the noble examples of Asmaul Husna. Objective: This study aimed to improve students’ learning outcomes through the use of video-based learning media on the noble exemplary values of Asmaul Husna in Islamic Religious Education at SD Negeri 41 Bengkulu Tengah. Method:  This study employed a classroom action research method conducted in 2024. Data were collected using observation, learning outcome tests, and documentation. Data analysis was conducted by measuring students’ mastery of learning. Result: The application of video-based learning media in Islamic Religious Education significantly improved students’ learning outcomes. An increase in learning mastery was observed from Cycle I to Cycle II. Finding:  Video media enhanced students’ engagement, understanding, and motivation in learning the noble, exemplary values of Asmaul Husna, thereby contributing to improved academic achievement. Conclusion: The use of video-based instruction on the noble exemplary values of Asmaul Husna was effective in improving students’ learning outcomes in Islamic Religious Education. Contribution: This study provides empirical and practical contributions for elementary school teachers by demonstrating the effectiveness of video-based learning media as an instructional strategy to improve learning outcomes.